Health, vulnerability, and energy: Assessing energy markets and consumer agency in New Zealand. (September 2016) - Lawson, Rob; Robertson, Kirsten; Wooliscroft, Ben
Abstract: Vulnerable consumers are defined as those at a disadvantage in a market place because they are not in control of their situation in a market exchange. We examine the self-efficacy of consumers who require the use of additional energy for medical reasons. Using data from two household national surveys in New Zealand carried out in 2011 and 2014 we demonstrate that medically vulnerable consumers have lower levels of self-efficacy in relation to energy decisions than non-medically vulnerable consumers. Consumers with low self-efficacy are less likely to manage their situation effectively. Current policy in New Zealand and elsewhere in the world requires vulnerable consumers to take action themselves which is less likely with low self-efficacy.